Early life stress and hippocampal neurogenesis in the neonate: sexual dimorphism, long term consequences and possible mediators - Lajud, Naima; Torner, Luz (Frontiers in Molecular Neuroscience, 2015)
Adverse early life experience decreases adult hippocampal neurogenesis and results in increased vulnerability to neuropsychiatric disorders. Despite that the effects of postnatal stress on neurogenesis have been widely studied in adult individuals, few efforts have been done to evaluate its immediate effects on the developing hippocampus. Moreover, it is not clear whether postnatal stress causes a differential impact in hippocampus development in male and female neonates that could be related to emotional deficits in adulthood. It has been proposed that the long term effects of early stress exposure rise from a persistent HPA axis activation during sensitive time windows; nevertheless the exact mechanisms and mediators remain unknown. Here, we summarize the immediate and late effects of early life stress on hippocampal neurogenesis in male and female rat pups, compare its later consequences in emotionality, and highlight some relevant mediator peptides that could be potentially involved in programming.